Automated Computation of the Instantaneous Velocity Centers of Planar Linkages (Determinación Automatizada de los Centros Instantáneos de Velocidad de Mecanismos Planos) (Jóvenes en la Ciencia, 2021)
This document presents a summary of the activities carried out during the XXVI Science Summer (XXVI Verano de laCiencia). Since the group had an international student, from India, whose native language is English, it was decided tosubmit at least some of the documents in English. The project included two related but different topics: The automatedcomputation of the instantaneous velocity centers of planar determinate linkages, and the determination of theinstantaneous velocity centers of two-degree of freedom planar linkages. Both topics are related to the topics includedin reasonable courses on planar kinematics but are usually beyond the topics usually included in those courses.Furthermore, the topics are of enough current interest to produce results that can be published in internationalscholarly journals.